Discovery of 5′′‐Chloro‐N‐[(5, 6‐dimethoxypyridin‐2‐yl)methyl]‐2, 2′:5′, 3′′‐terpyridine‐3′‐carboxamide (MK‐1064): A Selective Orexin 2 Receptor Antagonist (2‐SORA) for the Treatment of Insomnia. Issue 2 (27th December 2013) - Roecker, Anthony J.; Mercer, Swati P.; Schreier, John D.; Cox, Christopher D.; Fraley, Mark E.; Steen, Justin T.; Lemaire, Wei; Bruno, Joseph G.; Harrell, C. Meacham; Garson, Susan L.; Gotter, Anthony L.; Fox, Steven V.; et al.
Abstract The field of small‐molecule orexin antagonist research has evolved rapidly in the last 15 years from the discovery of the orexin peptides to clinical proof‐of‐concept for the treatment of insomnia. Clinical programs have focused on the development of antagonists that reversibly block the action of endogenous peptides at both the orexin 1 and orexin 2 receptors (OX1R and OX2R), termed dual orexin receptor antagonists (DORAs), affording late‐stage development candidates including Merck's suvorexant (new drug application filed 2012). Full characterization of the pharmacology associated with antagonism of either OX1R or OX2R alone has been hampered by the dearth of suitable subtype‐selective, orally bioavailable ligands. Herein, we report the development of a selective orexin 2 antagonist (2‐SORA) series to afford a potent, orally bioavailable 2‐SORA ligand. Several challenging medicinal chemistry issues were identified and overcome during the development of these 2, 5‐disubstituted nicotinamides, including reversible CYP inhibition, physiochemical properties, P‐glycoprotein efflux and bioactivation. This article highlights structural modifications the team utilized to drive compound design, as well as in vivo characterization of our 2‐SORA clinical candidate, 5′′‐chloro‐N‐[(5, 6‐dimethoxypyridin‐2‐yl)methyl]‐2, 2′:5′, 3′′‐terpyridine‐3′‐carboxamide (MK‐1064), in mouse, rat, dog, and rhesus sleep models.